2010
DOI: 10.1371/journal.pone.0015657
|View full text |Cite
|
Sign up to set email alerts
|

Galanin Receptor 1 Deletion Exacerbates Hippocampal Neuronal Loss after Systemic Kainate Administration in Mice

Abstract: BackgroundGalanin is a neuropeptide with a wide distribution in the central and peripheral nervous systems and whose physiological effects are mediated through three G protein-coupled receptor subtypes, GalR1, GalR2, and GalR3. Several lines of evidence indicate that galanin, as well as activation of the GalR1 receptor, is a potent and effective modulator of neuronal excitability in the hippocampus.Methodology/Principal FindingsIn order to test more formally the potential influence of GalR1 on seizure-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Also, it was reported that both GalR1 and GALR2 could mediate anticonvulsant effects of galanin (Mazarati & Lu, 2005). Similar to this study, GALR1 deficiency could influence susceptibility to KA-induced injury in C57BL/6J mice (Schauwecker, 2010). …”
Section: Discussionsupporting
confidence: 81%
“…Also, it was reported that both GalR1 and GALR2 could mediate anticonvulsant effects of galanin (Mazarati & Lu, 2005). Similar to this study, GALR1 deficiency could influence susceptibility to KA-induced injury in C57BL/6J mice (Schauwecker, 2010). …”
Section: Discussionsupporting
confidence: 81%
“…Increased neuronal loss in hippocampus after kainic acid administration (Schauwecker, 2010 (Brunner et al, 2014) Double GAL 1 Â GAL 2 -KO (Jacoby et al, 2002) Â Deltagen (San Carlos, CA)/C57BL/6J Â (129 ⁄ Svx C57BL/6) Galanin had no effect on GABAergic IPSPs in CeA neurons (decreased in WT) (Bajo et al, 2012) ACh, acetylcholine; bp, base pairs; CGRP, calcitonin gene-related peptide; CPZ, cuprizone; DBH, dopamine b-hydroxylase; EGFP, green fluorescent protein; GH, growth hormone; GI, gastrointestinal; Hbg, human b-globulin; IGF, insulin-like growth factor; lacZ, b-galactosidase; PDGF, platelet-derived growth factor; PSNI, partial saphenous nerve ligation injury; PVN, paraventricular nucleus of the hypothalamus; SNL, spinal nerve ligation. 126 2011, 2012), chronic constriction nerve injury (Nahin et al, 1994), orofacial pain (Tokunaga et al, 1992), exercise (Legakis et al, 2000), electroconvulsive stimulation (Christiansen, 2011), and herpes simplex virus infection (Henken and Martin, 1992).…”
mentioning
confidence: 99%
“…Schauwecker's group has explored this hypothesis but has found no compelling evidence in this regard (Schauwecker, 2003a(Schauwecker, ,b, 2010b. However, another receptor family, the galanin receptors, has been found to have an intriguing role in hippocampal development and plasticity (Burazin et al, 2000) and several lines of evidence (although the data are somewhat contradictory) support a role for the galanin receptor 1 (GalR1) in neuroprotection in status epilepticus (Mazarati et al, 2004;Schauwecker, 2010a). First, Schauwecker and colleagues (Schauwecker et al, 2004) found a distal region on chromosome 18, that includes the GalR1 locus, houses a quantitative trait locus that significantly influences susceptibility to kainic acid-induced cell death (called,Sicd1).…”
mentioning
confidence: 99%
“…This region was further refined using FVB.B6-Sicd1 lines of mice and the GalR1 locus remained with the region (Lorenzana et al, 2007). Second, recent evidence has demonstrated that GalR1 mRNA is differentially expressed in the hippocampus of sensitive (FVB) and resistant (B6) strains under baseline conditions (Kong et al, 2008;Schauwecker, 2010a). Third, Schauwecker (2010a) provided more direct evidence for the protective role of GalR1 by injecting an antagonist of GalR1 which resulted in increased cell death in the hippocampus following KA in the resistant B6 strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation